The Polish EU presidency in selected Greek media - Papadopoulou, Dora (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The main purpose of this article was to cover the most important news presented by the Greek media (SKAI Television, www.skai.gr, www.aixmi.gr, Kiriakatiki Eleftherotipia, www.avgi.gr and www.eleftherotypia.gr) about the Polish presidency from a quantitative perspective – (reporting only the most essential results because of lack of space). The rotating Polish presidency was a fact that received special attention – more or less – in almost every aspect (politics, economy, culture, international issues, etc.). Via those themes, the pieces of the jigsaw eventually completed the picture of different events that characterised the Polish presidency, which allows us to have a picture of its course over this period of six months. Apart from the key issues that those media addressed, it is worth mentioning both their critical view and the attitude that was adopted towards Poland.